1999
DOI: 10.1016/s1010-7940(98)00285-1
|View full text |Cite
|
Sign up to set email alerts
|

The threshold for air leak: stapled versus sutured human bronchi, an experimental study

Abstract: Hand sutured bronchi tolerated higher inflation pressure compared with the stapled ones before leaking air. Air leak at high pressure occurs in the presence of intact staples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 16 publications
2
12
0
3
Order By: Relevance
“…This period lasts 7-14 days in pedicled muscle flaps (6,7). During this critical revascularization period, the mechanical integrity of the bronchial stump is crucial for maintaining an air and water-tight barrier between the residual space and the remaining lung to avoid aspiration and mediastinal shifting following resection (8). Our study showed that, during the early period, bronchial stump coverage was associated with a better mechanical integrity than observed with uncovered stump, even if the healing process was omitted.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…This period lasts 7-14 days in pedicled muscle flaps (6,7). During this critical revascularization period, the mechanical integrity of the bronchial stump is crucial for maintaining an air and water-tight barrier between the residual space and the remaining lung to avoid aspiration and mediastinal shifting following resection (8). Our study showed that, during the early period, bronchial stump coverage was associated with a better mechanical integrity than observed with uncovered stump, even if the healing process was omitted.…”
Section: Discussionmentioning
confidence: 66%
“…However, no significant difference was found in a subsequent in vivo study (12). EL-GAMEL et al reported that, compared with stapled sutures, hand sutured bronchi tolerated higher inflation pressures before air leakage occurred (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly encountered complication of pneumonectomy in humans is BPF, which is described as a pathologic connection between the bronchus and pleural space [2,3,18,19,21,31-33,36]. Closure failure of the bronchial stump (BS) after partial or complete lung resection is the primary cause of BPF in humans, leading to a prolonged hospitalization period and the need for multiple operations [1,11,16-18,19,21,31-34,36]. Some authors [1,3,8] have reported of the incidence of BPF to be in the range of 0-28%, while others [19,21,31,32,34,35,37] have reported the incidence to be between 0% and 12%.…”
Section: Introductionmentioning
confidence: 99%
“…The mortality rate of BPF has been reported to be between 15% and 70% [8,10,14,16,18-20,37]. Pneumonia, pleural infections and failure in BS closure are the primary risk factors for BPF [1,11,17,19,32]. The proper BS closure technique to prevent BS dehiscence after pneumonectomy has been long debated in the field of human thoracic surgery [3,17,31].…”
Section: Introductionmentioning
confidence: 99%